Analysis of Potency of Advertisement Tax Toward The Regional Own-Source Revenue in Malang City - Andriadi, Bagus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Advertisement tax is one of local tax components which is expected to increase Malang local revenue and increase the welfare of its societies. This study aimed to analyze the potential, the realization of revenue and the effectivity of advertisement tax during the last 5 years as well as the efforts made by Local Revenue Office in order to improve the effectiveness of taxes. This research used descriptive quantitative method, where analysis was used to find the description of potential advertisement tax value and effectiveness of Malang Local Revenue Office. The results obtained in this study was the calculation of potential advertisement tax revenue for the years 2010 to 2014 showed that the potential advertisement tax in Malang had not been achieved optimally. Advertisement tax has high potential revenues. While the tax effectiveness of Local Revenue Office had been categorized as highly effective performance. In addition, efforts after the implementation of Malang Mayor Regulation No. 34 of 2013 in 2014 had showed positive results for the advertisement tax revenue in Malang.Â Keywords: Advertisement Tax, Potency Revenue, Tax Effectiveness, Own-Source Revenue, Local Tax